A Computational Justice Model for Dynamic Resource Allocation in Ad Hoc Networks - Juan Pablo Ospina; Joaquín Fernando Sánchez (Complex Systems Informatics and Modeling Quarterly)
Ad hoc networks are self-organizing systems that operate without a centralized controller or orchestration mechanism. As a result, it is not possible to apply allocation methods designed for centralized systems, which typically require complete information and aim to optimize overall system performance without accounting for the individual interests of network members. To address this challenge, we propose a computational justice model for dynamic resource allocation, drawing on socially inspired computing and agent-based modeling. The model integrates stochastic games, the concept of social institutions, principles of distributive justice, and adaptive strategies to design an allocation mechanism guided by fairness and cooperation. A central contribution of this work is the conceptual integration of these components into a unified framework that supports dynamic resource allocation in decentralized environments. We evaluated our proposal through simulation and compared its performance with previous works. The results show that the proposed model ensures the endurance of available resources and maintains cooperative behavior among network members, even in the presence of selfish behaviors. These findings suggest that the proposed model is a potential solution for addressing dynamic allocation problems in ad hoc networks.